2001
DOI: 10.1034/j.1600-0528.2001.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries patterns and oral health behaviors in Arizona infants and toddlers

Abstract: Dental caries was a significant health issue for these children under 3 years of age, and factors other than bottle feeding may play an important role in its etiology. Prevention of dental caries in children under age three will depend on a better understanding of the etiology as well as improved access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 13 publications
3
83
1
5
Order By: Relevance
“…There are no differences in the incidence of caries on the mesial and distal surfaces of the first and second molar. 14,21 In the present study, the incidence of dental caries on the proximal surfaces of the molars was higher. In the maxilla and mandible, caries mostly involved distal surfaces of the first molars than mesial surfaces.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…There are no differences in the incidence of caries on the mesial and distal surfaces of the first and second molar. 14,21 In the present study, the incidence of dental caries on the proximal surfaces of the molars was higher. In the maxilla and mandible, caries mostly involved distal surfaces of the first molars than mesial surfaces.…”
Section: Discussionmentioning
confidence: 69%
“…12 In accordance with previous findings it was found that tooth decay in young children mainly occurs on occlusal surfaces. 12,14,18,23,25,29 In these children, a small number of proximal surfaces are affected by caries, and if the disease develops, it begins after reaching complete contact between the first and second molar, at the age of 3.5 years. There are no differences in the incidence of caries on the mesial and distal surfaces of the first and second molar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence (and incidence) of dental caries in preschool children can be very high, as was illustrated in several studies [1][2][3][4][5]. According to a recent review on dental caries experience in young children, prevalence data for 5-yearolds varied between 29% in Denmark, 39% in Norway, 40% in England and Wales, 43% in Greece and 55% in Scotland [6].…”
Section: Introductionmentioning
confidence: 99%